iADAB- learning islamic etiqquette with augmented reality / Nurul Nadiah Ahmad Khadhri - Ahmad Khadhri, Nurul Nadiah (2019)
Today, information and technology are widely used especially in the education sector. The problem faced by the kindergarten students is that the traditional method of learning will make the students become less paying attention during class session. This situation will make it difficult for the teacher to attract and retain interest in the learning session. Basically, this project is about the development of Learning Islamic Etiquette with Augmented Reality (iAdab) application for kindergarten students. The objectives of this project are to identify the user requirements of iAdab application, to design and to develop iAdab application for the kindergarten students by following the ADDIE model methodology throughout the development process. The scope of this project is for the kindergarten students aged from 4-6 years old at Tadika Islam Sungai Manik Teluk Intan. They will learn the Islamic Etiquette which is adab while eating with augmented reality. There are three types of adab scenes while eating which are adab before eat, during eat and after eating. The software used to develop the mobile app is Unity and Android Studio, while the programming language used is JAVA, C#, and XML. This application use marker-based detection technology that requires image target to be a marker. When the marker is detected, the 3D model is rendered and can be overlaid on the marker’s position. This project will benefit teachers and parents as additional tools to teach children about Islamic manners at home and school. The future recommendation for this project is to include another adab scene such as adab with parents and another adab besides adab while eating and also available for iOS platform. In conclusion, iAdab AR application may assist children to understand the values and apply the learning later.